The Effectiveness of Mini Research Application on Contextual Learning Based for Students’ Attitude at Microbiology Subject - Hasruddin Hasruddin; Fauziyah Harahap; Mahmud Mahmud (Proceedings of AICS - Social Sciences, 2017)
The objective of this study was to find out the effect of mini research application on contextual learning based for students’ attitude at microbiology subject in State University of Medan. A quasi experimental research with pretest-posttest control group design was used in this study. The population of this study was 6th semester students of biology department and 2 classes chosen as the sample by applying cluster random sampling technique. Experimental class was using mini research application on contextual learning based while control class was using direct learning. The instrument used to obtain the data of students’ attitude was description questionnaire. The data were analysed by using Mann-Whitney U-Test with used Statistical Package for Social Science (SPSS) 22. The score of attitude were significantly from two classes, that U =78.64, n1 = 35, n2 = 34, p = 0.05, and z = 6.327 1.96 means the null hypothesis was rejected, suggesting that there is an effect of mini research application on contextual learning based for students’ attitude. Therefore, it can be stated that mini research application on contextual learning based as a more effective for students’ attitude in State University of Medan